Proceedings of the International Conference on Special and Inclusive Education (ICSIE 2018) 2019
DOI: 10.2991/icsie-18.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gadget Usage on Speaking Ability of 3-6 Year Olds

Abstract: The advanced technology makes information very accessible. The evolution of technology has revolutionized society including early childhood, but it is slowly destroying the ancient pattern itself. Indonesian children in the millennium generation are no longer familiar with traditional games because of the easy access of various games in the gadget. When using gadgets, children become less involved in interacting and communicating. Checking the current lifestyle is worrying. Children today have been adopted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Telah banyak ditemukan penelitian yang menyatakan efek negatif dari penggunaan gadget, antara lain dapat berpengaruh terhadap pola interaksi dan komunikasi siswa (Syahudin, 2019). Penelitian serupa juga menyatakan bahwa terlalu banyak menggunakan gadget dapat menghambat perkembangan komunikasi pada anak usia dini (Nasikhah & Purwanta, 2019). Terlebih lagi jika lingkungan sosial anak dihuni oleh para pecandu gadget dapat berimplikasi buruk terhadap perkembangan mental emosional maupun psikologis siswa.…”
Section: Kondisi Lingkungan Sosial Anakunclassified
“…Telah banyak ditemukan penelitian yang menyatakan efek negatif dari penggunaan gadget, antara lain dapat berpengaruh terhadap pola interaksi dan komunikasi siswa (Syahudin, 2019). Penelitian serupa juga menyatakan bahwa terlalu banyak menggunakan gadget dapat menghambat perkembangan komunikasi pada anak usia dini (Nasikhah & Purwanta, 2019). Terlebih lagi jika lingkungan sosial anak dihuni oleh para pecandu gadget dapat berimplikasi buruk terhadap perkembangan mental emosional maupun psikologis siswa.…”
Section: Kondisi Lingkungan Sosial Anakunclassified
“…Laily & Chandra (2021) also stated that children who are addicted to the internet tend to play alone, are less sensitive to the environment and become individualized individuals. Another problem when children are addicted to gadgets is the disruption of the child's speaking ability (Nasikhah & Purwanta, 2019). So it can be concluded that children who are addicted to gadgets will have an impact on social relationships and emotional and mental feelings, children tend to be individual individuals, are not good at socializing with their surroundings, have problems with children's speaking skills and prefer to play with gadgets than playing with friends.…”
Section: Introductionmentioning
confidence: 99%